2016 IEEE Global Communications Conference (GLOBECOM) 2016
DOI: 10.1109/glocom.2016.7842049
|View full text |Cite
|
Sign up to set email alerts
|

On the Computation of Centrality Metrics for Network Security in Mesh Networks

Abstract: Betweenness centrality is a popular metric in social science, and recently it was adopted also in computer science. Betweenness identifies the node, or the nodes, that are most suitable to perform critical network functions, such as firewalling and intrusion detection. However, computing centrality is resourcedemanding, we can not give for granted that it can be computed in real time at every change in the network topology. This is especially true in mesh networks that generally use devices with few computatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Likewise, centrality measures are studied in the context of network security. For instance, they have been used to configure distributed firewalls [25] and to identify critical nodes in which intrusion detection and firewalling is most suitable [26]. In addition, they were applied to build cloud-based filters and footprints of traffic inspection algorithms at global scrubbing centers [27].…”
Section: Centrality In Computer Networkmentioning
confidence: 99%
“…Likewise, centrality measures are studied in the context of network security. For instance, they have been used to configure distributed firewalls [25] and to identify critical nodes in which intrusion detection and firewalling is most suitable [26]. In addition, they were applied to build cloud-based filters and footprints of traffic inspection algorithms at global scrubbing centers [27].…”
Section: Centrality In Computer Networkmentioning
confidence: 99%
“…Conversely, a new node can be added to G' to perform collusion between two sub-groups in a design. We can calculate BC of a node as follows [18]:…”
Section: Definitions and Terminologymentioning
confidence: 99%
“…Leveraging Puzis' heuristic it is possible to show that, even using a very low-power device, the exact computation can be carried out for networks made of hundreds of nodes in just a few seconds [5]. We exploit this result to further study how sensitive the betweenness metric is to topology changes in…”
Section: A Centrality In Networkmentioning
confidence: 99%
“…The first step to design Prince was to implement Puzis' heuristic and test its performance on real hardware. Preliminary results have shown that for a network made of 236 nodes, a low-cost wireless router (an Ubiquiti M5 wireless router, equipped with a MIPS 390MHz processor and 32M of RAM) requires 7 seconds to compute the centrality of each node using Puzis' heuristic, less than 1 3 of the time required by Brandes' algorithm [5].…”
Section: A Implementing Puzis' Heuristicmentioning
confidence: 99%
See 1 more Smart Citation